2016
DOI: 10.1111/cei.12767
|View full text |Cite
|
Sign up to set email alerts
|

Complement activation in leprosy: a retrospective study shows elevated circulating terminal complement complex in reactional leprosy

Abstract: SummaryMycobacterium leprae infection gives rise to the immunologically and histopathologically classified spectrum of leprosy. At present, several tools for the stratification of patients are based on acquired immunity markers. However, the role of innate immunity, particularly the complement system, is largely unexplored. The present retrospective study was undertaken to explore whether the systemic levels of complement activation components and regulators can stratify leprosy patients, particularly in refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…These proteins are related but not directly involved in the leprosum clot formation, because high levels of both proteins were also observed in leprosy patients sera weeks prior to leprosum clot occurrence. It was already demonstrated that complement activation products are highly abundant in leprosy reactional episodes, and their presence in the leprosum clot is probably circumstantial [ 41 ]. IHRP, which is also increased in patient’s sera and blood clot, belongs to the inter-alpha-trypsin inhibitor family of acute phase proteins, comprising the common light chain bikunin.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are related but not directly involved in the leprosum clot formation, because high levels of both proteins were also observed in leprosy patients sera weeks prior to leprosum clot occurrence. It was already demonstrated that complement activation products are highly abundant in leprosy reactional episodes, and their presence in the leprosum clot is probably circumstantial [ 41 ]. IHRP, which is also increased in patient’s sera and blood clot, belongs to the inter-alpha-trypsin inhibitor family of acute phase proteins, comprising the common light chain bikunin.…”
Section: Discussionmentioning
confidence: 99%
“…Delays in diagnosis of reactions directly translate into negative clinical outcomes, as associated neuropathy not properly diagnosed or treated within the first 6 months of symptoms will likely become permanent 20 alongside the disabilities it may later initiate via recurrent ulcers and other related pathologies 21 . Despite recent scientific progress with respect to complement 22,23 and serum-proteins, particularly CXCL10 (IP-10), as biomarkers associated with onset of reactions 1517,2426 , discovery of accurate, clinically useful prognostic biomarkers remains elusive, leaving early diagnosis of reactions a currently unmet need.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to APPs, components of the complement system (e.g., C3b, C4b, and iC3b) and immunoglobulins opsonize molecules to promote phagocytosis (114). Notably, terminal complement complex (TCC) and iC3b of the complement system are valuable for the stratification of leprosy patients with or without T1R (115).…”
Section: Acute-phase Proteins and Cortisolmentioning
confidence: 99%